E-satisfaction as a mediator between consumer loyalty and E-CRM: The context of Lebanese e-commerce - Younis, Joumana A; Al-Shammari, Hameed; Hejase, Hussin Jose; Massoud, Mazen; Hejase, Ale Jose (International Journal of Innovative Research and Scientific Studies, 2024)
This article’s purpose is to assess the influence of E-CRM on consumer loyalty through satisfaction. Electronic customer relationship management E-CRM is a marketing tool used to manage consumer loyalty. However, the adoption of outdated E-CRM strategies increases dissatisfaction and attrition rates. That is, to assess the effect of perceived quality online, online customization, and customer trust on loyalty from online shoppers’ perspectives. This quantitative explanatory study begins with an exploratory factor analysis to simplify the concept’s dimensions. A questionnaire was distributed to a sample of Lebanese customers as a measurement instrument. Data analysis used factor analysis, followed by confirmatory factor analysis (CFA) using a structural model,and later regression. EFA is a fundamental prerequisite to CFA. Then, principal factor analysis (PCA) verified items for each construct dimension. The removal of items with low contributions improved the value of the KMO test, variance explained, and internal reliability measured with Cronbach’s alpha, which increased to 0.865. PCA extracted factors by restoring a minimum of 50% of the variance. The CFA relies on normed indices, sustaining the adjustment of the theoretical structure. Absolute fit criteria are highlighted: the RMSEA, GFI, and AGFI. Findings supported the idea that E-CRM strategies concentrating on online service quality, online presence, customization, and customer trust develop e-satisfaction and loyalty. Effective E-CRM satisfies customers and increases their e-satisfaction, leading to higher levels of loyalty. These outcomes increase awareness about the strategic value of E-CRM to businesses, and the paper serves as an eye-opener for future researchers and marketing experts.